2017
DOI: 10.5606/tftrd.2017.453
|View full text |Cite
|
Sign up to set email alerts
|

Does electrodiagnostic evidence correlate with mood and function in patients with a pre-diagnosis of carpal tunnel syndrome?

Abstract: Objectives: This study aims to investigate if function and mood involvement correlate in female patients who have a pre-diagnosis of carpal tunnel syndrome (CTS) and its correlation with physical examination and electrodiagnostic findings. Patients and methods:A total of 170 patients between the ages of 18-65 who applied to Physical Medicine and Rehabilitation outpatient clinics with CTS symptoms between May 2014 and December 2015 were enrolled. The mean age of patients was 44.6±11 years. Before electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These results indicated that the said patient group had high levels of health anxiety and somatosensory amplification. In comparison, in another study available in the literature the CTS patients were divided into groups based on their EMG findings as normal, mild, moderate or severe, however no significant difference was found between these groups in terms of BDI, VAS, and the disabilities of the arm, shoulder and hand (DASH) questionnaire scores 5 . In this study, only BDI was used for psychological assessment.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…These results indicated that the said patient group had high levels of health anxiety and somatosensory amplification. In comparison, in another study available in the literature the CTS patients were divided into groups based on their EMG findings as normal, mild, moderate or severe, however no significant difference was found between these groups in terms of BDI, VAS, and the disabilities of the arm, shoulder and hand (DASH) questionnaire scores 5 . In this study, only BDI was used for psychological assessment.…”
Section: Discussionmentioning
confidence: 89%
“…In parallel with the results of these studies, Coskun et Al. have determined a positive correlation between the VAS scores with BDI scores 5 . There are also studies available in the literature in which a relationship has been demonstrated between chronic pain and depression 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations